The potential of phosphate solubilizing bacteria isolated from sugarcane wastes for solubilizing phosphate - A Atekan; Y Nuraini; E Handayanto; S Syekhfani (Brawijaya University, 2014)
Most of P in agricultural soils is in unavailable forms for plant growth. Phosphate solubilizing bacteria can increase soil P availability. This study was aimed to isolate phosphate solubilizing bacteria from sugarcane waste compost and to test ability of the isolated bacterial to dissolve phosphate. The bacteria were isolated from three types of sugarcane waste, i.e. filter cake compost, bagasse compost, and a mixture of filter cake + bagasse + trash biomass compost. The potential colony was further purified by the Pikovskaya method on selective media. Eight isolates of phosphate solubilizing bacteria were obtained from all wasted studied. Amongst them, T-K5 and T-K6 isolates were superior in dissolving P from Ca3(PO4)2 in the media studied. The two isolates were able to solubilize P with solubilizing index of 1.75 and 1.67 for T-K5 and T-K6, respectively. Quantitatively, T-K6 isolate showed the highest P solubilization (0.74 mg / L), followed by T-K5 isolate (0.56 mg / L), while the lowest P solubilization (0.41 mg / L) was observed for T-K4 isolate. The increase of soluble P was not always followed by the decrease in pH.